2018
DOI: 10.1007/s00284-018-1446-8
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms Developed on Dental Implant Titanium Surfaces with Different Roughness: Comparison Between In Vitro and In Vivo Studies

Abstract: Microbial biofilms developed on dental implants play a major role in perimplantitis' pathogenesis. Many studies have indicated that surface roughness is the main feature favoring biofilm development in vitro, but its actual influence in vivo has still to be confirmed. In this study, the amount of biofilm formed on differently treated titanium surfaces, showing distinct roughness, has been examined both in vivo and in vitro by Confocal Laser Scanning Microscopy. In vitro studies availed of biofilm developed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 26 publications
4
38
0
1
Order By: Relevance
“…Coinciding with our findings, Bevilacqua et al [43] recently examined the amount of biofilm formed on differently treated titanium surfaces both in situ and in vitro by CLSM. Unlike the results observed in the in- vitro biofilm, in-situ experiments showed no difference in the amount of biofilm formed on the different surfaces after a 24-h incubation in the mouth of healthy volunteers.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Coinciding with our findings, Bevilacqua et al [43] recently examined the amount of biofilm formed on differently treated titanium surfaces both in situ and in vitro by CLSM. Unlike the results observed in the in- vitro biofilm, in-situ experiments showed no difference in the amount of biofilm formed on the different surfaces after a 24-h incubation in the mouth of healthy volunteers.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike the results observed in the in- vitro biofilm, in-situ experiments showed no difference in the amount of biofilm formed on the different surfaces after a 24-h incubation in the mouth of healthy volunteers. Consequently, these authors concluded that quantitative differences observed in- vitro models among surfaces with distinct roughness may not be predictive of different colonisation rates in situ [43]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed rough surfaces display irregular topography, which protect bacteria against shear forces during their initial reversible binding. Many previous works have reported a high positive correlation between surface roughness and bacterial adhesion . Quantitative observation by CFU/mL showed a clear and direct proportional growth of Streptococcus mutans according to the increased roughness values .…”
Section: Current Biomaterial‐based Solutions To Prevent Peri‐implantitismentioning
confidence: 70%
“…The progress of precision medicine indicates that similar progress has been made in the field of oral orthodontics, and will gradually be applied to realize personalized and customized treatment methods and improve treatment efficiency . The objective of previous research was to provide a context for the development of computer technology and biomedical science.…”
Section: Applications Of 3d Printing In Dentistrymentioning
confidence: 99%